Pembuatan Video Iklan Fatayya Craft Sebagai Media Promosi di Sosial Media Menggunakan Aplikasi Adobe Premier dan Adobe After Effect - Defira Putri Pangesta; Mamok Andri Senubekti (Melati Institute, 2023)
The development of technology in the modern era as it is now has a major impact on progress in the business world. To achieve the goals of the business being run, it is necessary to make an effective strategy, one example is through an advertisement. Advertising will provide information to the general public. Ads are used to provide information to the public about goods, services and businesses that are run. Ads can be made using multimedia elements, where there are combining elements of images, sound, video, text and animation to create a video ad and this is appropriate as a promotional effort for fassion businesses and accessories such as Fatayya Craft.Seeing Fatayya Craft's target market is those among young people and women. Based on this, this is an opportunity to make an advertising video, which aims to promote the Fatayya Craft business through social media, where video advertising functions as informative advertising, this advertisement is included in commercial advertising.